Development of Al-Qur'an and Hadith Modules to Improve Students' Understanding of Long Readings - Sinta Titis Pangesti Putri Ciptami; Suwarno Suwarno; Muhammad Hatta; Ismet Nur; Salman Zahidi; Ahmad Saddad (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
One of the problems that often occurs in learning is students' inability to understand the existing teaching materials, so that the learning process is hampered. To overcome this obstacle, it is necessary to develop teaching materials that are appropriate to students' needs. The purpose of this development research is to apply the ADDIE model of teaching material development while also testing and implementing it in learning. Data collection using interviews, observations, questionnaires, and tests. Data analysis using qualitative descriptive analysis and quantitative analysis. The findings of this study are that the development steps using the ADDIE model were carried out sequentially from the first step to the last step, paying attention to the substance of each step. The teaching materials resulting from this development were categorized as very valid based on the assessment of material experts with a score of 4.8 and media experts with a score of 4.7. For effectiveness, the effective category is based on the results of pre-tests and post-tests in the use of developed teaching materials, with high significance of 70% and moderate significance of 30%.